The get personal application to improve personal safety skills in children - Yun Nina Ekawati; Verdiantika Annisa; Nofrans Eka Saputra (HUMANITAS published by Universitas Ahmad Dahlan., 2023)
Sexual crime comprises child sexual abuse, grouping, rape, or the torture of a person in a sexual manner. Recently, sexual crimes have posed a threat to children in Indonesia. This study aimed to determine the effectiveness of the Get Personal application in enhancing children's personal safety skills against sexual crime. A pre-post control group design was utilized with a quasi-experimental approach. Twenty-two elementary school pupils who participated in the study were split into experimental and control groups, with the experimental group receiving the Get Personal application treatment. The personal safety skills scale was utilized to obtain the pretest and posttest data. The data were analyzed by independent sample t-test and paired sample t-test. Significant differences were found in the results of personal safety skills in the pretest and posttest scores in the experimental group, while the control group didn’t indicate any difference. Following the paired t-test, individuals in the experimental group demonstrated a significant difference between the means of the pretest and posttest, with the posttest’s mean score being higher than the pretest’s mean score. Therefore, the Get Personal application improves children's personal safety skills and may apply to enhance personal safety skills among children.